Youth perspectives on marine debris management through a community empowerment approach: A case study of a student workshop and its environmental impact - Rachman, Indriyani; Matsumoto, Toru (Interaction, Community Engagement, and Social Environment, 2025)
inadequate ventilation system can increase the risk of sick building syndrome symptoms. This study aims to analyze the most significant risk factors with symptoms of sick building syndrome in workers at PT X. Methods: The study used a cross-sectional study design, and the data was processed with the chi-square test and multiple logistic regression tests with a sample of all production area workers at PT X. A total of 91 workers included in this study. Carbon monoxide, temperature, humidity, PM10 and formaldehyde were measured using a particle counter and wind speed was measured using an anemometer. Measurements were taken at 17 different points. Findings: The results showed that 85 out of 91 workers (93.4%) experienced symptoms of sick building syndrome. There is a relationship between temperature (p-value=0.013) and wind speed (p-value=0.031) symptoms of sick building syndrome. The most dominant variable is the formaldehyde (POR=0.457). Conclusion: It is concluded that the variables associated with symptoms of sick building syndrome are temperature and wind speed, with formaldehyde being the most dominant. The company is advised to monitor indoor air quality regularly and improve the ventilation system at the production area. Novelty/Originality of this Study: This study provides valuable insights into the relationship between environmental factors such as temperature, wind speed, and formaldehyde with sick building syndrome symptoms in a production environment, highlighting the need for regular indoor air quality monitoring and improved ventilation systems to safeguard worker health.